Determination of γ-D-glutamyl-meso-diaminopimelic acid in rumen fluid of dairy cows by pre-column chiral derivatization-HPLC. Issue 6 (18th November 2022) - Wang, Yan; Gao, Qianyun; Cheng, Xiaoye; Chang, Guangjun; Roy, Animesh Chandra; Shen, Xiangzhen
Abstract: High concentrate (HC) diet feeding leads to the lysis of rumen microbes and the release of hazardous metabolites, which can trigger inflammatory responses, thereby impairing dairy cow health and production. γ -D-glutamyl- meso -diaminopimelic acid (iE-DAP), which constitutes the peptidoglycan (PGN) layer of bacteria, is the minimum PGN structure capable of activating inflammatory signaling pathways. This research paper aimed to determine the iE-DAP concentration and investigate the effects of an HC diet on the concentration of iE-DAP in the rumen fluid of dairy cows. However, there are limited studies on the determination of iE-DAP concentration. Hence, we established a high-performance liquid chromatography (HPLC) method combined with pre-column chiral derivatization to detect the concentration of iE-DAP in rumen fluid. Moreover, we conducted an animal experiment that included 12 lactating Holstein cows, which were randomly divided into a low-concentrate (LC) group and an HC group. The results showed that the linear range of iE-DAP was 5–500 µg/mL and that the intra- and inter-day RSDs were lower than 7%. Meanwhile, this method was successfully applied to the analysis of iE-DAP in rumen fluid, and the results revealed that long-term feeding with an HC diet elevated the concentration of iE-DAP in rumen fluid of dairy cows.